QUALITY EVALUATION OF FRESH RUTABAGA - Glebova S.Y.; Golub O.V. (Техника и технология пищевых производств)
The diet of a modern man should contain fruits and vegetables as producers of physiologically active substances. However, rutabaga - primordial Russian vegetable - has been unfairly forgotten in the range of this product group. At present this root crop is mainly used in fodder production. The purpose of the research is quality evaluation of fresh ripened rutabaga grown in the households of the Novosibirsk region. The aim is achieved by fulfilling the following tasks: determination of conformity of products to the requirements of normative documentation (in appearance; internal structure; the size of roots in the greatest transverse diameter; the amount of roots with minor mechanical damage of the pulp or the skin, slight healed cracks, surface damage of skin with pests (rodent damage is not permitted), with petioles longer than the established size, with deviations in size; the presence of the soil adhered to the roots; the presence of frozen, decaying roots; determination of the main organoleptic parameters (size, correct shape, visual appeal, the intensity and uniformity of color, consistency of epithelial tissues and pulp, aroma and taste), as well as chemical composition. We have used common research methods (organoleptic and physical-chemical ones), the results being processed with software products. It has been established that rutabaga tested for three years meets the regulatory requirements in terms of regulated indices and its organoleptic evaluation proves its excellent quality. It has been revealed that the chemical composition of rutabaga is consistent with the average literature data. Studied rutabaga can be used as food when reviving Russian cuisine.